Building back fairer from the COVID-19 pandemic in South Africa - Arndt, Channing; Davies, Robert J.; Gabriel, Sherwin; Harris, Lawrence; Sachs, Michael (South African Reserve Bank, 2023)
On 27 August 2019, National Treasury released a document titled ‘Economic transformation, inclusive growth, and competitiveness: A contribution towards a growth agenda for the South African economy’. Perhaps as a response to the long title, the document became popularly known as “the 77-pager”. No document that proposes a substantial reform economic programme is universally embraced; however, the 77-pager did receive some important plaudits. For example, The Economist magazine described it as “replete with sensible ideas that could form the basis of a new ‘growth strategy’” (The Economist 2019). National Treasury (2019) estimated that the proposed reforms would, following implementation, raise potential growth by 2.3 percentage points (above the baseline) and create over 1 million additional jobs.